Flavonols Induced by 5-Aminolevulinic Acid Are Involved in Regulation of Stomatal Opening in Apple Leaves - Longbo LIU; Lijun XIONG; Yuyan AN; Jie ZHENG; Liangju WANG (Horticultural Plant Journal, 2016)
Flavonols, the main flavonoids in plant leaves, have newly been proposed as a H2O2 scavenger in guard cells. However, whether 5-aminolevulinic acid (5-ALA) is involved in regulating stomatal movement of apple (Malus × domestica Borkh. ‘Fuji’) leaves through flavonol accumulation remains unclear. In this study, using diphenylboric acid 2-amino ethyl ester (DPBA, a flavonol fluorescent dye) and a laser scanning confocal microscope, we observed that 5-ALA pretreatment significantly improved flavonol accumulation in guard cells of apple leaves, especially around the nucleus. Then we demonstrated that 5-ALA pretreatment inhibited ABA-induced stomatal closure via decreasing reaction oxygen species (ROS) accumulation in guard cells. Pretreatment with quercetin or kaempferol, two main kinds of flavonols in plants, also inhibited ABA-induced stomatal closure by decreasing ROS content in the guard cells. Furthermore, exogenous flavonols could suppress H2O2-induced stomatal closure in apple leaves. Taken together, we conclude that ALA-induced flavonol accumulation in guard cells is involved in the inhibitory effect of ALA on ABA-induced ROS accumulation and stomatal closure in apple leaves.